PENGEMBANGAN BUDAYA MUTU DALAM MENINGKATKAN KUALITAS MADRASAH DI MADRASAH IBTIDAIYYAH NEGERI KOTA BANDAR LAMPUNG - Anwar, Syaiful (Universitas Islam Negeri Raden Intan Lampung, 2014)
DEVELOPING A QUALITY CULTURE IN IMPROVING QUALITY OF MADRASAH (Studies in MIN as Bandar Lampung): Quality is important in human life, both individually, comunally, or socially. Quality can be guaranteed by ensuring that each individual has a capacity needed to carry out the job properly. With the right tools, workers will be able to make products and services in a manner consistent with the costumer expectations. Quality improvement is a continuous process and without ending. At the institutional level, the development of quality requires the seriousness of all school board members and administrators along with a mass training which allows each individual in school to be trained. This study explores the quality culture improvement patterns which are applied in the State Madrasah Ibtidaiyyah of Bandar Lampung. Through a qualitative descriptive approach, this research is expected to give a contribution in improving the quality of Islamic education in general.